The Perception of Geography Teacher Candidates on the Board Game as a Media to Increase Learning Interaction Quality - Harsono, H; Wahyudi, Tri Nur; Wardana, Zaid Ali (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
In the recent years, there has been a concern on how to make an innovative learning in the classroom in order to provide supportive learning environment. Such learning environment can be constructed in which it also highly relates to the learning media used by the teacher. Learning media are utilized to transfer lesson into easier way before it was delivered to the students. The main objective of this research was to describe the perception of teacher candidates who were still in the undergraduate degreeregarding with the use of board game as one of the learning media. This research was quantitative research and utilized questionnaire to collect the data. The objects of this research were 129 teacher candidates in the Department of Geography Education, Faculty of Teacher Training and Education at Universitas Muhammadiyah Surakarta. The questionnaires were distributed in two days by using simple random sampling by the method of accidental sampling in which it was given to the teacher candidates who came to the lecturer. Descriptive statistics was used to interpret the data. In general, the teacher candidates perceived the potential of the board game as a learning media in order to increase the interaction between teachers and students in the classroom. The teacher candidates also had sufficient understanding on the implementation of the board game.